A dynamic theory of communication - Gomes, Orlando , 1964- (Nova Science Publishers, 2009)
Communication is a dynamic and complex process. The study of human communication introduces us to a world of multiple scenarios, agents, variables and interconnections, which are important to understand. This book focuses on the notion of dynamic process. It considers techniques of intertemporal analysis and optimal control.